ANALISIS PENGARUH FAKTOR-FAKTOR SOSIAL EKONOMI TERHADAP PENDAPATAN NELAYAN DI WADUK GAJAH MUNGKUR, KABUPATEN WONOGIRI, JAWA TENGAH - Pangesti, Lintang; Sofiati, Dwi (Inisiasi, 2025)
Fishermen's income is influenced by various complex factors, including social and economic aspects. The absence of specific studies related to fishermen's income in Gajah Mungkur Reservoir indicates the need for further analysis. The aim of this study is to analyze the influence of socio-economic factors on fishermen's income in Gajah Mungkur Reservoir, Wonogiri Regency, Central Java. This study was conducted in three sub-districts located on the west side of the reservoir, namely Wonogiri Sub-district, Wuryantoro Sub-district, and Eromoko Sub-district. The sampling technique used cluster random sampling with 88 respondents. The methods used were income analysis and multiple regression. The results showed an average income of Rp39,181,092 and net income of Rp27,244,896 per year. Socio-economic variables in the study influenced 62% of income. Simultaneously, the independent variables had a significant effect, partially only the level of education, age, and operational costs were significant. Institutional participation and market access are not significant.